Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to show that the process

$Y(t) = e^t \int_0^t e^{-s}dW(s)$ satisfies the following SDE:

$dX(t) = X(t)dt + dW(t), \ \ t\geq 0 , \quad X(0) = 0$

I think the right approach is to use Ito's formula, but i don't see how. I thought that the argument $dW(s)dt = 0$ is totally wrong in the direct approach. If one would try Ito's formula, $f$ would be $Y(t) = f(t,X(t)) = e^t \int_0^t e^{-s}dX(s)$, where $X(t) = W(t)$, the brownian motion. Now if we try to calculate $dY(t)$ with Ito, we get:

$\frac{\partial f}{\partial t} = tY(t)$ (?)

$\frac{\partial f}{\partial X} = X(t)$

$\frac{\partial^2 f}{\partial X^2} = dX(t)$

Could you give me a hint on how to do this? Thanks!

share|cite|improve this question

If we set $$Z(t) := \int_0^t e^{-s} \, dW_s,$$ then $Z_t$ is a Itô process. Moreover, $dZ_t = e^{-t} \, dW_t$. If we apply Itô's formula to

$$f(t,z) := e^t \cdot z,$$

we obtain

$$\begin{align*} \underbrace{f(t,Z_t)}_{Y_t}-\underbrace{f(0,0)}_{0} &= \int_0^t \underbrace{e^s}_{\partial_z f(s,Z_s)} \, dZ_s + \int_0^t (\underbrace{e^s \cdot Z_s}_{\partial_t f(s,Z_s)} + \underbrace{0}_{\partial_z^2 f(s,Z_s)}) \, ds \\ &= \int_0^t \, dW_s + \int_0^t Y_s \, ds \\ \Leftrightarrow dY_t &= dW_t + Y_t \, dt \end{align*}$$

using that $Y_t = f(t,Z_t)$ by definition.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.